2019
DOI: 10.3389/fpubh.2019.00374
|View full text |Cite
|
Sign up to set email alerts
|

Local Health Department Accreditation Is Associated With Organizational Supports for Evidence-Based Decision Making

Abstract: Introduction: Recent studies show that health department accreditation from the U.S. Public Health Accreditation Board (PHAB) drives performance management and quality improvement. PHAB standards call for agencies to use evidence in decision making. It is unknown whether accreditation is associated with organizational supports for evidence-based decision making (EBDM). Self-report data from a 2017 survey of U.S. local health departments were analyzed to test relationships of accreditation status with organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…27 Researchers have also found that people working in accredited health departments were more likely to report that they had the ability to use evidence-based decision making within their work and had the resources and evaluation capabilities to conduct such practices. 28 Regardless of the underlying reason, and despite the growth over the past decade, our findings highlight room for improvement in whether and how much LHDs generate and use evidence to inform their service offering. Thus, an important question still remains: how to support LHDs' use of EBPs?…”
Section: Discussionmentioning
confidence: 79%
“…27 Researchers have also found that people working in accredited health departments were more likely to report that they had the ability to use evidence-based decision making within their work and had the resources and evaluation capabilities to conduct such practices. 28 Regardless of the underlying reason, and despite the growth over the past decade, our findings highlight room for improvement in whether and how much LHDs generate and use evidence to inform their service offering. Thus, an important question still remains: how to support LHDs' use of EBPs?…”
Section: Discussionmentioning
confidence: 79%
“…In addition to the presence of the CHIP, accredited local health departments are fertile ground for exploring the application of implementation science to specific topics. Allen et al‘s study of 350 local health departments found that accreditation was associated with two key features: awareness of and capacity for evidence-based decision making [ 9 ]. CHIPs are an already existing tool explicitly intended to guide communities in addressing priority public health issues through a combination of evidence-based and policy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…10 These include improved and implemented new quality improvement (QI) and performance management efforts; strengthened partnerships; improved internal and external transparency and accountability; improved workforce training and development; and improved utilization of resources. 11 Studies have found that accredited LHDs were more likely to report higher capacity for evidence-based decision making and evaluation than health departments that were not yet preparing for PHAB accreditation, 12 and accredited LHDs are more likely to report new funding as a result of accreditation, improved staff competencies, and new opportunities for partnerships and collaboration. 13 Given the barriers to applying and the relatively low rate of application for accreditation among smaller LHDs, there is a need to explore how the experiences and benefits of accreditation differ across LHDs of different sizes.…”
mentioning
confidence: 99%